The Effectiveness of Multisensory-Based Busy Book Learning Media to Improve Reading Ability of Students with Special Needs at SDN 01 Inclusion Sowan Lor - Fadzali, Hamidaturrohmah (Jurnal Gentala Pendidikan Dasar, 2023)
Student with special needs require assistance and media in achieving their best condition. One of them is by using busy book media which is used as a means of improving the early reading skills of children with mild intellectual disabilities. This study aims to test the effectiveness of Busy Book media on the initial reading ability of student with special needs with intellectual disabilities. This study used single subject research with an A-B-A design and research data analysis using visual graph analysis techniques. Data analysis showed baseline (A1) of initial reading ability was carried out for 4 days with a mean of 50% and a fixed tendency of direction and data changes continued with intervention for 4 days with a mean of 88.75%. The tendency of direction increases and the change in data increases then the researcher performs a baseline (A2) carried out for 4 days with a 100% mean and a fixed direction tendency and changes in fixed data and overlape data that has a low percentage. The result of this study is that busy book learning media is effective in improving early reading skills for children with mild intellectual disabilities at SDN Inclusion 1 Sowan Lor